THE EFFECTIVENESS OF USING WORDWALLS TO IMPROVE STUDENTS' UNDERSTANDING OF INDONESIAN CULTURAL DIVERSITY MATERIAL - Ani Setianingsih; Anik Widiastuti; Agustina Tri Wijayanti; Suranto Suranto (STKIP PGRI Tulungagung, 2026)
This study aims to investigate the effectiveness of the Wordwall interac-tive learning media in improving fifth-grade students' understanding of the topic